KARYAWAN DI HOTEL PANGERAN BEACH PADANG - Rahima, Witri; Silfeni, Silfeni; Abrian, Youmil (Journal of Home Economics and Tourism, 2015)
This study aimed to determine the effect Compensation Employee Motivation In Hotel Pangeran Beach Padang. This research is associative causal research. With the entire employee population Pangeran Beach Hotel Padang, amounting to 97 employees. The selection of the study sample using nonprobability sampling with sampling technique saturated. Collecting data using a questionnaire based on Likert Scale which has been tested for validity and reliability. The study concluded that the overall compensation belong to the category of a bad job with the percentage of 35%, and on each indicator is sufficient salary in the category with a percentage of 35%, incentives in both categories with a percentage of 30%, and facilities in both categories with a percentage 31%. As for the motivation toÂ work quite well belong to the category with a percentage of 40%, and on each indicator is persistence in the category quite well with the percentage of 42%, the excitement of working in a category quite well with the percentage of 29%, labor discipline in the category quite well with percentage of 34%, the responsibility in both categories with a percentage of 35%. These results indicate a positive and significant influence between compensation and employee motivation at Hotel Pangeran Beach Padang where the value of 17.615 t> t table 1.985. Thus Ha stating there is influence between compensation and work motivation can be received with great influence of 76.6%, while 23% were alleged motivation is influenced by other factors.